Four New Cytotoxic Arborinane-Type Triterpenes from the Endolichenic Fungus Myrothecium inundatum - Basnet, Buddha Bahadur; Liu, Li; Chen, Baosong; Suleimen, Yerlan Melsuly; Yu, Haiyang; Guo, Shouyu; Bao, Li; Ren, Jinwei; Liu, Hongwei (Planta Medica, 2019)
Two new arborinane-type triterpenes, myrotheols A (1) and B (2), two new arborinane-type glycosides, myrothesides C (3) and D (4), together with four known diterpenes (5 – 8) were isolated from the ethyl acetate extract of the endolichenic fungus Myrothecium inundatum. The structures of new compounds 1 – 4 were elucidated by NMR and MS analyses. The absolute configuration of 1 was assigned by a single-crystal X-ray diffraction experiment. Compounds 3 and 4 represent the first two natural 4-O-methyl-α-D-mannosides. Compounds 1 – 8 exhibited cytotoxicity against K562 and RKO human cancer cell lines.
Keywords: endolichenic fungi; Myrothecium inundatum; Stachybotryaceae; arborinane-type; riterpenes; diterpenes; cytotoxicity